PENGENALAN EKONOMI DAN BISNIS ISLAM MELALUI PENCEGAHAN PENYEBARAN VIRUS COVID-19 DI DESA CIMANGGU I, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Wahyu Irhamna (SAHID EMPOWERMENT JOURNAL, 2022)
Community service activities carried out in Cimanggu I Village, Cibungbulang District, Bogor Regency, from July to August 2020, were adjusted to the circumstances of the Covid-19 pandemic. The condition of rural communities which are currently in a limited condition along with large-scale social restrictions, still needs to be given enthusiasm and hope that things will change for the better in the future as long as they remain in faith and Islamic beliefs. Islam as a perfect view of life certainly has a wide space as a basis for prayer and effort, moreover Islam encompasses all matters of life, including in terms of Islamic economics and business. Thus, rural communities need to be refreshed regarding Islam, especially with the concept of Islamic economics and business which can raise enthusiasm in the midst of an atmosphere of limitations due to the Covid-19 pandemic. Therefore, in community service activities which include providing counseling on preventing the spread of the Covid-19 virus, counseling is also given in the form of an introduction to Islamic economics and business to the community.